2004
DOI: 10.1071/wr02031
|View full text |Cite
|
Sign up to set email alerts
|

Determining the distribution and abundance of a regional koala population in south-east Queensland for conservation management

Abstract: Koala surveys were used to determine the distribution and abundance of a threatened regional koala population in south-east Queensland to assist with the development of effective conservation management programs. Daytime systematic searches of strip transects were conducted twice yearly from 1996 to 1999 to determine koala density at a number of sites in urban, remnant bushland and bushland strata. Mean density estimates for 27 survey sites ranged from 0.02 to 1.26 koalas ha–1. Koala densities were generally h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…The key to the survival of urban koalas may be their ability to exploit patchy resources and find a mate in a fragmented landscape, but this may also increase the chance that they will suffer trauma from vehicles and dogs (Backhouse and Crouch 1990;Cork et al 2000;Phillips 2000;Dique et al 2004). Our findings are consistent with other studies that have shown a high probability of trauma for koalas moving in and through fragmented and heavily urbanised areas in south-east Queensland (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The key to the survival of urban koalas may be their ability to exploit patchy resources and find a mate in a fragmented landscape, but this may also increase the chance that they will suffer trauma from vehicles and dogs (Backhouse and Crouch 1990;Cork et al 2000;Phillips 2000;Dique et al 2004). Our findings are consistent with other studies that have shown a high probability of trauma for koalas moving in and through fragmented and heavily urbanised areas in south-east Queensland (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Koala populations in south-east Queensland are experiencing rapid reductions in range (Dique et al 2003a(Dique et al , 2004. This decline has mostly been attributed to habitat fragmentation (Martin and Handasyde 1999) and loss through clearing for agriculture and urban development (Cogger et al 2003;Sullivan et al 2004;Gordon et al 2006;Lane 2008;DERM 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys that count koalas through direct observation take many person hours and, although they are used in the more densely populated east coast koala populations and in smaller study areas (Gordon et al 1990;Melzer and Lamb 1996;Dique et al 2004), they are not practical for large areas with low-density populations (Sullivan et al 2002). Faecal pellet surveys are a well-established method of determining koala presence, and thus distribution and habitat selection (Phillips and Callaghan 2000;McAlpine et al 2006b).…”
Section: Faecal Pellet Surveysmentioning
confidence: 99%